Challenges and Opportunities in Career Development Planning for Functional Officers in Sikka Regency: A Study Based on the Strategic Planning for Human Resources Framework - Rentika Konstantin Karwayu; Sumartono; Mohammad Nuh (The Journal of Indonesia Sustainable Development Planning, 2025)
This study aims to analyze the career development planning of functional officials serving as Human Resource Analysts at BKPSDM of Sikka Regency through the perspective of Strategic Planning for Human Resources (SPHR), and to identify its supporting and inhibiting factors. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The findings reveal that the planning process remains unstrategic, not based on job requirements, and lacks participation from functional civil servants. The absence of a grand strategy, limited capacity of planners, non-analytical information systems, and budget constraints are identified as the primary obstacles. Meanwhile, the merit system policy, motivation of functional civil servants, and emerging managerial awareness serve as potential enabling factors. This study recommends strengthening the planning institution, formulating strategic documents, digitizing career mapping, and integrating policies based on competence and performance as key solutions to sustainably reform the career system of functional civil servants.